Growth all along the road? Personality development and international contacts of (in)experienced sojourners. Issue 4 (July 2021) - Zimmermann, Julia; Greischel, Henriette; Jonkmann, Kathrin; Neyer, Franz J.
International student mobility (ISM) is an important educational means to promote the international (job market) potential of university students. Beyond that, it constitutes a context of personality development in young adulthood. With the present research, we tried to integrate the perspectives of applied and personality research in addressing the following questions. First, we scrutinized the robustness of ISM effects on personality development as we controlled for effects of sociodemographic characteristics and implemented a waiting group design ( N  = 3070). Second, we explored ISM anticipation effects as well as the moderation of ISM effects by previous international mobility experiences. Finally, in view of the public discourse on the benefits of "Erasmus crowds", we assessed the roles of international and host relationships with regard to the personality development of sojourners. The results largely corroborated the robustness of ISM effects on personality development. No ISM anticipation effects occurred, and effects of current ISM engagement were largely unaffected by previous international mobility experiences. Finally, international contact experiences were associated with personality development above and beyond effects of host country contacts. Implications for the understanding of personality development and potential inferences for the organization and improvement of ISM programs are discussed.